Criticism of the Philosophy of Liberation - Rengifo-Carpintero, John Alexis; Díaz-Caicedo, Carmen Helena (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The article is a critical reflection on the ideological phenomenon of the South, called, Philosophy of Liberation. In this, three aspects are analyzed: first, the exacerbated use of historical reflection above all positive happenings; Second, his doxological pretension that ends up being a Judaization of thought in Latin America; And third, the terrible paradox that this way of thinking offers: the application of a decolonial method necessarily implies a place of power from where the oppressed judges the history and the world of the life of the oppressor. The proposed methodology for this examination is the deconstructive, orientation action that will allow us to highlight the conceptual contradictions of such a movement. For this, the text makes a reflection on two movements that gave origin to him, the Critical Pedagogy and the Liberation Theology. Finally, the text shows the contradictions of this way of thinking, presenting the decolonial action as a norm to be applicable to any historical process of exclusion, marginalization and colonization, producing a discourse of power which has been determined to reject.